Ženstvena-da, svakako! Feministkinja-nikako! - Potkonjak, Sanja (2004)
This paper is a "feminist" portrait of Croatian educationalist, ethnographer, and writer Jelica Belović Bernadzikowska (1870-1946).Her importance arises from less known work on "feminine question." The paper aims at analysing popular writings of JBB, pointing to the paradox of maternal feminism discussed in her work.
Projekt MZOS
ENG